P134 Exercise Responses to One-legged Cycling in Patients with Idiopathic Pulmonary Fibrosis. (12th November 2015) - Reilly, TS; Majd, S; Popat, B; Greening, NJ; Dolmage, TE; Agrawal, S; Woodhead, FA; Evans, RA
Abstract : Introduction: Pulmonary Rehabilitation is recommended for patients with Idiopathic Pulmonary Fibrosis (IPF) although the magnitude of benefit appears less compared to those with other chronic lung diseases. Patients with IPF may not be able to sustain high-intensity training to induce physiological change due to a ventilatory limitation to exercise. One strategy to circumvent this in COPD has been to reduce the exercising muscle mass by cycling one leg at a time during the same exercise session. Randomised controlled trials have shown greater improvements in exercise capacity after training using one-legged cycling (OLC) compared to two-legged cycling (TLC). 1, 2 We, therefore, compared OLC to TLC responses during incremental and constant work rate (CWR) exercise in patients with IPF. Methods: Patients were recruited from a tertiary referral centre if they met the current NICE diagnostic criteria for IPF with a MRC dyspnoea grade ≥2. Exclusion criteria included a requirement for long-term oxygen therapy. Participants completed four Cardiopulmonary Exercise Tests (CPETs) to intolerance on a cycle ergometer with expired gas analysis. The tests were completed on separate days: 1) two-legged maximal incremental test (TLC-ICE); 2) one-legged maximal incremental test (OLC-ICE); 3) two-legged CWR (TLC-CWR) test at 70% peak power achieved on the TLC-ICE; 4) one-legged CWR (OLC-CWR) test at 35% TLC-ICE peak power. Results: Twelve participants (11 male, mean [SD] 73 [8] yrs, BMI 30.6 [4.8] kg/m 2, FVC% predicted 71.8 [20.3]%, resting SpO2 98 [1]%) completed all four CPETs demonstrating a ventilatory limitation to exercise (92 [14]% maximum voluntary ventilation [MVV]). Although the OLC-ICE peak oxygen uptake (peak VO2 ) was significantly lower than the peak VO2 TLC-ICE (p < 0.001) the OLC: TLC was high at 0.85. The OLC-CWR was endured for more than twice the TLC-CWR (p < 0.001) at the same muscle-specific power leading to almost double the work being performed (Table 1 ). Conclusion: OLC at the same muscle-specific power compared to TLC enabled patients with IPF to achieve almost double the work in a simulated exercise training session. Future research should investigate OLC as a potentially efficacious aerobic training strategy for patients with IPF. References: 1 Bjorgen SJ. Eur J ApplPhysiol 2009;106 :501–507 2 Dolmage TE. Chest 2008;133 :370–376